An Interactive Study of Learning Environment and Teacher Characteristics on Value-added Performance of Higher Vocational College Students (Journal of Interdisciplinary Insights, 2024)
This study investigates the interactive effects of the learning environment and teacher characteristics on the value-added performance of higher vocational college students. The research employs a quantitative research design, utilizing cross-sectional survey data from 280 students at Shandong XX College. The study explores key dimensions of the learning environment and teacher characteristics and their impact on student outcomes. Results indicate significant positive correlations between the learning environment, teacher characteristics, and value-added performance. Multiple regression and structural equation modeling analyses reveal direct and indirect effects of the learning environment and teacher characteristics on student performance. Findings underscore the importance of creating supportive learning environments and investing in teacher development to enhance student outcomes in vocational education settings.